Analysis of Student's Problem Solving Ability On Quadrilateral and Triangular Matter - Puji Lestari; Nurrochim Nurrochim (Afeksi: Jurnal Penelitian dan Evaluasi Pendidikan, 2020)
The aim to be achieved in this study is to determine the level of problem-solving ability possessed by VII grade students on rectangular and triangular material in MTs Negeri 2 Magelang 2019/2020 academic year based on Polya's steps in solving problems. This type of research is a qualitative study using a descriptive approach. Sampling in this study used purposive sampling, namely 4 students of class VII H and 3 students of VII I of MTs Negeri 2 Magelang in the academic year 2019/2020. Data sources from primary sources and secondary sources. Data collection procedures using interviews, documentation and tests (giving mathematical problem solving questions). Data analysis techniques using the Miles and Huberman model, namely data reduction, data presentation, and verification. Checking the validity of the data uses the theory triangulation technique. The results showed that the level of problem solving skills in grade VII students was very good, evidenced by students being able to solve problems with the four steps of problem solving Polya, a) understanding the problem, b) compiling a plan for solving, c) carrying out the plan, and d) checking back. The fourth level is the highest level of problem solving ability from the existing level.